UJI EFEKTIVITAS ANTIJAMUR EKSTRAK KULIT JERUK PURUT (Citrus hystrix) TERHADAP PERTUMBUHAN JAMUR Aspergillus niger dan Candida albicans - Christine Wira Dika Halawa; Ester Mendrofa; Yuliani Lubis (Universitas Negeri Medan, 2019)
Kaffir lime (Citrus hystrix) is an herbal plant and is quite well known by Indonesian people who have various benefits. Kaffir lime is commonly used as a flavoring food while the skin is usually discarded by the community. It turns out that kaffir lime skin has medicinal properties and can cure diseases, there are various kinds of addictive substances or chemical compounds that have the effectiveness as an antifungal.This study aims to determine the inhibition of kaffir lime peel extract on the growth of Aspergillus niger and Candida albicans with concentrations of 25%, 50%, 75%, 100%. This type of research is an experimental laboratory with disc diffusion method.The results showed that kaffir lime extract (Citrus Hystrix) had a very strong effectiveness of antifungal Aspergillus niger and Candida albicans, which at a concentration of 100% reached 22.20 mm in Candida albicans and 26.36 mm in Aspergillus niger.In this study showed that kaffir lime extract (Citrus hystrix) has antifungal effectiveness. Because it reaches the ideal diameter inhibition zone according to the classification of response to inhibition of fungal growth. The higher the concentration of extract given, the greater the antifungal inhibitory power.